Hematopoietic Stem Cell Regulation by Type I and II Interferons in the Pathogenesis of Acquired Aplastic Anemia - Smith, Julianne N. P.; Kanwar, Vikramjit S.; MacNamara, Katherine C. (Frontiers in Immunology, 2016)
Aplastic anemia (AA) occurs when the bone marrow fails to support production of all three lineages of blood cells, which are necessary for tissue oxygenation, infection control, and hemostasis. The etiology of acquired AA is elusive in the vast majority of cases but involves exhaustion of hematopoietic stem cells (HSC), which are usually present in the bone marrow in a dormant state, and are responsible for lifelong production of all cells within the hematopoietic system. This destruction is immune mediated and the role of interferons remains incompletely characterized. Interferon gamma (IFNγ) has been associated with AA and type I IFNs (alpha and beta) are well documented to cause bone marrow aplasia during viral infection. In models of infection and inflammation, IFNγ activates HSCs to differentiate and impairs their ability to self-renew, ultimately leading to HSC exhaustion. Recent evidence demonstrating that IFNγ also impacts the HSC microenvironment or niche, raises new questions regarding how IFNγ impairs HSC function in AA. Immune activation can also elicit type I interferons, which may exert effects both distinct from and overlapping with IFNγ on HSCs. IFNα/β increase HSC proliferation in models of sterile inflammation induced by polyinosinic:polycytidylic acid and lead to BM aplasia during viral infection. Moreover, patients being treated with IFNα exhibit cytopenias, in part due to BM suppression. Herein, we review the current understanding of how interferons contribute to the pathogenesis of acquired AA, and we explore additional potential mechanisms by which interferons directly and indirectly impair HSCs. A comprehensive understanding of how interferons impact hematopoiesis is necessary in order to identify novel therapeutic approaches for treating AA patients.